Respuesta :
Answer:
b = -2
Step-by-step explanation:
Equation-
y = 3x + b
Values-
x = -2
y = 4
By substituting the value of x and y, we get,
4 = -3 ( -2 ) + b
4 = 6 + b
-b = 6 - 4
-b = 2
b = -2
Hope the answer was helpful!!
Regards..
The value of b is = -2
- The calculation is as follows:
The equaton is y = 3x + b
Here
x = -2
y = 4
Now put the x and y value to the given equation
So,
4 = -3 ( -2 ) + b
4 = 6 + b
-b = 6 - 4
-b = 2
b = -2
Learn more: https://brainly.com/question/13981855?referrer=searchResults